More food with less water – Optimizing agricultural water use. (January 2019) - Smilovic, Mikhail; Gleeson, Tom; Adamowski, Jan; Langhorn, Colin
Highlights: Crop kites quantifies the potential of optimizing irrigation water. Spatiotemporal redistribution of water can significantly increase water productivity. Basin-wide management of water can significantly increase water productivity. Increasing water productivity by decreasing water use and increasing food production.